BRING ME: SUSTAINABLE URBAN DELIVERY SERVICE FOR THE CITY OF GRAZ - Trummer, Wolfgang; Hafner, Norbert (Advanced Logistic Systems - Theory and Practice, 2018)
A large proportion of urban transport results on private shopping. Alternatives to operate the first-/ last-mile-logistics for urban shopping in a sustainable manner are often missing. In August 2014 a new, environment friendly and sustainable delivery service for City center of Graz started - named “bring mE”. With this service, private shoppers have the opportunity to get their purchases delivered by cargo bicycles. The task of the ITL was to ensure a successful implementation of the delivery. For this purpose, the delivery service was evaluated after a period of 9 months and necessary improvement measures were derived.